How Evaluate Quality of Life among Rural Suburbs of Uromia - vahid gholizadeh ghale aziz; yarmohammad ghasemi; hossein mehdizadeh (توسعه اجتماعی, 2017)
This research has been conducted to identify and explore villagers’ expectations and views about the quality of life around Urmia. To this end, a qualitative method has been employed with an emphasis on grounded theory. Sampling method in this research was purposeful and theoretical. Theoretical saturation was used for reaching sample saturation (20 cases in this study). To analyze the data of this study, a three-step coding method was used. The first stage is open coding in which important concepts were extracted from each interview. The second stage was axial coding in which 20 important extracted categories were summarized. Then the axial categories were put in the paradigm pattern which was comprised of six components of causal conditions, phenomenon, contextual factors, confounding factors, strategies and outcomes. Finally, in the third stage which was selective coding, the core category or concept of "life quality erosion" was extracted. This category, as the grounded theory, covers and explains all the axial categories surrounding the quality of life in rural areas.